Production of biopolymer precursors beta-alanine and L-lactic acid from CO2 with metabolically versatile Rhodococcus opacus DSM 43205 - Salusjärvi, Laura; Ojala, Leo; Peddinti, Gopal; Lienemann, Michael; Jouhten, Paula; Pitkänen, Juha-Pekka; Toivari, Mervi (Frontiers in Bioengineering and Biotechnology, 2022)
Hydrogen oxidizing autotrophic bacteria are promising hosts for conversion of CO2 into chemicals. In this work, we engineered the metabolically versatile lithoautotrophic bacterium Rhodococcus opacus strain DSM 43205 for synthesis of polymer precursors. Aspartate decarboxylase (panD) or lactate dehydrogenase (ldh) were expressed for beta-alanine or L-lactic acid production, respectively. The heterotrophic cultivations on glucose produced 25 mg L-1 beta-alanine and 742 mg L-1 L-lactic acid, while autotrophic cultivations with CO2, H2 and O2 resulted in the production of 1.8 mg L-1 beta-alanine and 146 mg L-1 L-lactic acid. Beta-alanine was also produced at 345 µg L-1 from CO2 in electrobioreactors, where H2 and O2 were provided by water electrolysis. This work demonstrates that R. opacus DSM 43205 can be engineered to produce chemicals from CO2 and provides a base for its further metabolic engineering.